New practical results about adhesion limites obtained from experimental stand testing - Lata, Michael; Čáp, Jaroslav; Voltr, Petr (Univerzita Pardubice, 2009)
The concept of adhesion in the field of rail transport represents an ability of tractive force transmission between wheel and rail. Adhesion characteristics is a property of tangential forces transmission between wheel and rail and represents the dependence of tractive force T or adhesion coefficient μ on creep velocity w, or, divided by speed of travel, dependence on relative creep s. The ascending branch of adhesion characteristics is of great importance and acts as one of significant input parameters to drive regulation systems. It is needed to determine value of initial steepness (cTs or cμs) which is defined as an increment of tractive force or adhesion coefficient, respectively, related to a small increment of relative creep. Knowledge on the descending branch is no less important. Thorough understanding of related phenomena and limits of both parts of adhesion characteristics enables an effective exploitation of vehicle tractive and braking abilities. A theoretical model of the adhesion mechanism is briefly presented in the introduction to this paper. Following, description of a test stand of a tram wheel driven by a synchronous motor is given, as well as description of experiments conducted by the authors at it. Attention is paid to results of experimental research concerning identification of parameters of the ascending and the descending branch of adhesion characteristics. The paper summarizes this results and compares results of authors‘ own experiments to it.
Keywords: adhesion limites; regulation systems; experimental research